2021
DOI: 10.1249/mss.0000000000002781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise-induced Hypoalgesia and Its Neural Mechanisms

Abstract: Purpose: Exercise-induced hypoalgesia is frequently documented in the literature. However, the underlying neural mechanism of this phenomenon remains unclear. Here, we explored the effects of different intensities of isometric exercise on pain perception with a randomized controlled design and investigated its neural mechanisms through tracing the dynamic changes of heat-evoked brain responses. Methods: Forty-eight participants were randomly assigned to one of the three groups with different exercise intensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 55 publications
0
24
0
1
Order By: Relevance
“…However, the mechanism driving clinically meaningful changes in function requires a different form of engagement: time in the program. Exercise-induced analgesia is well documented in the literature, although the mechanism remains unclear [ 49 , 50 ]. We speculate that patients may associate exercise with pain reduction because they perceive a change in tissue status after stretching and movement.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism driving clinically meaningful changes in function requires a different form of engagement: time in the program. Exercise-induced analgesia is well documented in the literature, although the mechanism remains unclear [ 49 , 50 ]. We speculate that patients may associate exercise with pain reduction because they perceive a change in tissue status after stretching and movement.…”
Section: Discussionmentioning
confidence: 99%
“…Various exercises have been recommended to mitigate chronic pain, and different types of exercise produce different analgesic effects. [19][20][21][22][23] A quasi-experiment found that healthy women experienced an increase in PPTs after completing knee extension strength training, and the effect returned to baseline levels after 20-minute exercise even if the test sites were far from the area of active muscles. 24 Jones et al recruited 16 healthy adults to complete 20 minutes of moderateintensity aerobic exercise on a cycle ergometer, and the results showed a substantial increase in PPTs but not in heat pain thresholds after exercise.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that the incidence of neuropathic pain is far from being low, and neuropathic pain is worth investigating. However, thus far, only a few studies have revealed the exact mechanism and treatment methods despite the increase in research on neuropathic pain (11).…”
Section: Introductionmentioning
confidence: 99%